2007
DOI: 10.1118/1.2710949
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and stability of positioning in radiosurgery: Long term results of the Gamma Knife system

Abstract: The primary aim of this investigation was to determine the long term overall accuracy of an irradiation position of Gamma Knife systems. The mechanical accuracy of the system as well as the overall accuracy of an irradiation position was examined by irradiating radiosensitive films. To measure the mechanical accuracy, the GafChromic film was fixed by a special tool at the unit center point (UCP). For overall accuracy the film was mounted inside a phantom at a target position given by a two-dimensional cross. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 11 publications
0
29
0
2
Order By: Relevance
“…The automatic positioning system of Gamma Knife Model C or 4C provides an additional error of ± 0.2 mm [11]. Wu et al [24] showed that the measured mechanical accuracy of Gamma Knife Model U was 0.3 mm.…”
Section: Discussionmentioning
confidence: 98%
“…The automatic positioning system of Gamma Knife Model C or 4C provides an additional error of ± 0.2 mm [11]. Wu et al [24] showed that the measured mechanical accuracy of Gamma Knife Model U was 0.3 mm.…”
Section: Discussionmentioning
confidence: 98%
“…Relevant published studies have added scientific creditability to this belief and an accuracy level better than 0.5 mm is widely acknowledged within the GK user community irrespective of the specific model. [4][5][6][7] On the other hand, the MR-related spatial distortions, which have been recognized as a major contributor to GK geometric accuracy degradation, 4, 7-11 vary from system to system and depend on the gradient coil design, the magnetic field strength, and the particular imaging parameters. Over the recent years, a considerable body of work has been performed on image distortion measurement and correction techniques [12][13][14][15][16][17][18] in an effort to exploit the comparative advantages of MR relative to CT images for radiation treatment planning purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Reasons for the failure of stereotactic radiosurgery in achieving an adaequate tumor control include an inadequate visualization of the tumor, a lack of intraoperative 3-D (volumetric) imaging, or an insufficient or limited dose (e.g. due to proximity to the brainstem) [21,29,33,47,51,58,68,145,154]. …”
Section: Introduction/historymentioning
confidence: 99%